PHYSICAL AND VERBAL VIOLENCE IN INDONESIAN FOLKTALES RETOLD IN CHILDRENâS BOOKS - Masykuroh, Qanitah (Universitas Muhammadiyah Surakarta, 2016)
Folktales as a cultural expression can contain all aspects of human lifeÂ including violence. As Indonesia comprises so many diverse cultures, the contextof violence, its degree and its nature, are also various. This study examines theÂ forms of violence in Indonesian folktales, focusing on how physical and verbalÂ violence are depicted in Indonesian folktales retold in childrenâs books that wereÂ published in ten years of post-reformasi period. Content analysis is used to scrutinizeÂ the forms of violence. The finding shows that physical and verbal violenceÂ in Indonesian folktales retold as childrenâs storybooks is prevalent. I argue thatÂ the diverse forms and nature of violence presented in childrenâs story books illuminateÂ the connection between social and individual expressions of violence.Â This study provides a way to look at the structural and ideological function ofviolence in contemporary traditional folk literature.